Calcaneal Tendon Collagen Fiber Morphometry and Aging - Hadraba, Daniel; Janacek, Jiri; Filova, Eva; Lopot, Frantisek; Paesen, Rik; Fanta, Ondrej; Jarman, Anneliese; Necas, Alois; Ameloot, Marcel; Jelen, Karel (Microscopy and microanalysis, 2017)
Fibrillar collagen in tendons and its natural development in rabbits are discussed in this paper. Achilles tendons from newborn (~7 days) to elderly (~38 months) rabbits were monitored in intact (n tendons=24) and microtome sectioned (n tendons=11) states with label-free second harmonic generation microscopy. After sectioning, the collagen fiber pattern was irregular for the younger animals and remained oriented parallel to the load axis of the tendon for the older animals. In contrast, the collagen fiber pattern in the intact samples followed the load axis for all the age groups. However, there was a significant difference in the tendon crimp pattern appearance between the age groups. The crimp amplitude (A) and wavelength (Λ) started at very low values (A=2.0±0.6 µm, Λ=19±4 µm) for the newborn animals. Both parameters increased for the sexually mature animals (>5 months old). When the animals were fully mature the amplitude decreased but the wavelength kept increasing. The results revealed that the microtome sectioning artifacts depend on the age of animals and that the collagen crimp pattern reflects the physical growth and development.
Keywords: Aging; konfokální mikroskopie; Microscopy, Polarization; polarizační mikroskopie; Fibrillar Collagens; Biomechanical Phenomena; fibrilární kolageny; fiber orientation; extracelulární matrix; králíci; Microscopy, Confocal; collagen; biomechanika; Animals; Microscopy, Electron, Scanning; zvířata; Extracellular Matrix; pevnost v tahu; stárnutí; Rabbits; crimp; Achillova šlacha; Tensile Strength; mikroskopie elektronová rastrovací; aging; tendon; Achilles Tendon